Do the effects of strain and religiosity on criminal coping differ by race and ethnicity? - Babieri, Nina (Crime & delinquency, 2018)
Recently, Agnew suggested that delinquent offending is more likely to occur in the presence of a variety of criminogenic risk factors. Prior research has suggested that racial and ethnic differences exist in both the type and frequency of negative life experiences as well as coping mechanisms utilized in response to these strains. The current study sought to determine the relationship between prior victimization and a coping mechanism on subsequent offending, while controlling for the role of criminogenic risk factors. Racial and ethnic differences were also explored. Results revealed mixed support for general strain theory’s arguments on the unequivocal import of victimization as well as racial and ethnic differences in the impact of strain and religiosity on future offending. Future research considering criminal propensities and racial/ethnic differences are needed.